Power play: A multi-criteria analysis of present and future battery technologies - Aditya Anindito Widayat; Gregory J. Offer; Jacqueline S. Edge; Evangelos Kallitsis (Journal of Cleaner Production, 2026)

Adaptive area-wide management for suppressing spruce budworm outbreaks: effectiveness of the early intervention strategy - Rob C. Johns; S. Edwards; L. Amos-Binks; J. J. Bowden; D. Carleton; C. Edge; C. Hennigar; P. James; D. MacLean; V. Martel; E. R. D. Moise; B. Morin; et al. (Journal of Pest Science, 2026)
In eastern North America, two main insecticide-based strategies are used to manage spruce budworm ( Choristoneura fumiferana ) outbreaks. The traditional ‘Foliage Protection Strategy’ (FPS) focuses on temporarily reducing defoliation and tree mortality in high-value stands, allowing outbreaks to progress naturally in surrounding areas. The ‘Early Intervention Strategy’ (EIS) is an adaptive, area-wide management approach that targets low-density “hotspots” to prevent outbreak growth and spread. We report findings from a 10-year case study (2015–2024) in Atlantic Canada assessing EIS effectiveness. EIS treatments consistently reduced population growth rates, resulting in a 12–67% reduction in hotspot areas compared to untreated areas. Crucially, this suppression curbed the rise and spread of the outbreak across northern New Brunswick, with negligible defoliation observed throughout the study period. By comparison, in a neighboring Quebec study area contemporaneously managed with FPS, the outbreak advanced normally, causing moderate to severe defoliation over ~ 1.7 million hectares by 2024. Moreover, EIS required ~ 80% less insecticide, with 66% of treated areas receiving treatment in only a single year, compared with just 15% under FPS. Our findings provide robust evidence for the effectiveness of EIS when implemented under suitable conditions, highlighting its potential as a proactive outbreak management approach.

Irregular Shelterwood Methods for Achieving Ecological and Climate Adaptation Objectives in the Central Hardwood Forest Region - Miranda T. Curzon; John M. Lhotka; Tara L. Keyser; Gregory J. Edge; Bradley M. Hutnik; Jacob J. Muller; Jodi A. Forrester (Journal of Forestry, 2026)

Tree Planting for Climate Adaptation and Emerald Ash Borer in the Lake States, US: Motivations and State of the Practice - Lucia A. Fitts; Rebecca A. Montgomery; Brian J. Palik; Peter W. Clark; Josh Kragthorpe; Mike R. Reinikainen; Gregory J. Edge; Stephen Handler; Bradley M. Hutnik; Anthony W. D’Amato (Journal of Forestry, 2025)

Think global act local: The dependency of global lithium-ion battery emissions on production location and material sources - Evangelos Kallitsis; Jordan J. Lindsay; Mudit Chordia; Billy Wu; Gregory J. Offer; Jacqueline S. Edge (Journal of Cleaner Production, 2024)

Legacy community science data suggest reduced beached litter in response to a container deposit scheme at a local scale - Kay Critchell; Libby Edge; Michael J. Traurig (Marine Pollution Bulletin, 2023)

Portable gas chromatography–mass spectrometry method for the in-field screening of organic pollutants in soil and water at pollution incidents - Denise Duff; Chris Lennard; Yarong Li; Christopher Doyle; Katelyn J. Edge; Ian Holland; Kevin Lothridge; Paul Johnstone; Paul Beylerian; Val Spikmans (Environmental Science and Pollution Research, 2023)
Environmental pollution incidents generate an emergency response from regulatory agencies to ensure that the impact on the environment is minimised. Knowing what pollutants are present provides important intelligence to assist in determining how to respond to the incident. However, responders are limited in their in-field capabilities to identify the pollutants present. This research has developed an in-field, qualitative analytical approach to detect and identify organic pollutants that are commonly detected by regulatory environmental laboratories. A rapid, in-field extraction method was used for water and soil matrices. A coiled microextraction (CME) device was utilised for the introduction of the extracted samples into a portable gas chromatography–mass spectrometry (GC–MS) for analysis. The total combined extraction and analysis time was approximately 6.5 min per sample. Results demonstrated that the in-field extraction and analysis methods can screen for fifty-nine target organic contaminants, including polyaromatic hydrocarbons, monoaromatic hydrocarbons, phenols, phthalates, organophosphorus pesticides, and organochlorine pesticides. The method was also capable of tentatively identifying unknown compounds using library searches, significantly expanding the scope of the methods for the provision of intelligence at pollution incidents of an unknown nature, although a laboratory-based method was able to provide more information due to the higher sensitivity achievable. The methods were evaluated using authentic casework samples and were found to be fit-for-purpose for providing rapid in-field intelligence at pollution incidents. The fact that the in-field methods target the same compounds as the laboratory-based methods provides the added benefit that the in-field results can assist in sample triaging upon submission to the laboratory for quantitation and confirmatory analysis.

Water quality and health in northern Canada: stored drinking water and acute gastrointestinal illness in Labrador Inuit - Carlee J. Wright; Jan M. Sargeant; Victoria L. Edge; James D. Ford; Khosrow Farahbakhsh; Inez Shiwak; Charlie Flowers; Sherilee L. Harper (Environmental Science and Pollution Research, 2018)

Phenotypic plasticity of nest timing in a post‐glacial landscape: how do reptiles adapt to seasonal time constraints? - Christopher B. Edge; Njal Rollinson; Ronald J. Brooks; Justin D. Congdon; John B. Iverson; Fredric J. Janzen; Jacqueline D. Litzgus (Ecology, 2017)
Life histories evolve in response to constraints on the time available for growth and development. Nesting date and its plasticity in response to spring temperature may therefore be important components of fitness in oviparous ectotherms near their northern range limit, as reproducing early provides more time for embryos to complete development before winter. We used data collected over several decades to compare air temperature and nest date plasticity in populations of painted turtles and snapping turtles from a relatively warm environment (southeastern Michigan) near the southern extent of the last glacial maximum to a relatively cool environment (central Ontario) near the northern extent of post‐glacial recolonization. For painted turtles, population‐level differences in reaction norm elevation for two phenological traits were consistent with adaptation to time constraints, but no differences in reaction norm slopes were observed. For snapping turtle populations, the difference in reaction norm elevation for a single phenological trait was in the opposite direction of what was expected under adaptation to time constraints, and no difference in reaction norm slope was observed. Finally, among‐individual variation in individual plasticity for nesting date was detected only in the northern population of snapping turtles, suggesting that reaction norms are less canalized in this northern population. Overall, we observed evidence of phenological adaptation, and possibly maladaptation, to time constraints in long‐lived reptiles. Where present, (mal)adaptation occurred by virtue of differences in reaction norm elevation, not reaction norm slope. Glacial history, generation time, and genetic constraint may all play an important role in the evolution of phenological timing and its plasticity in long‐lived reptiles.

Microbes in beach sands: integrating environment, ecology and public health - Richard L. Whitman; Valerie J. Harwood; Thomas A. Edge; Meredith B. Nevers; Muruleedhara Byappanahalli; Kannappan Vijayavel; João Brandão; Michael J. Sadowsky; Elizabeth Wheeler Alm; Allan Crowe; Donna Ferguson; Zhongfu Ge; et al. (Reviews in Environmental Science and Bio/Technology, 2014)

Community vulnerability to the health effects of climate change among indigenous populations in the Peruvian Amazon: a case study from Panaillo and Nuevo Progreso - I. Hofmeijer; J. D. Ford; L. Berrang-Ford; C. Zavaleta; C. Carcamo; E. Llanos; C. Carhuaz; V. Edge; S. Lwasa; D. Namanya (Mitigation and Adaptation Strategies for Global Change, 2013)

Using genetic techniques to quantify reinvasion, survival and in situ breeding rates during control operations - A. J. Veale; K.‐A. Edge; P. McMurtrie; R. M. Fewster; M. N. Clout; D. M. Gleeson (Molecular Ecology, 2013)
Determining the origin of individuals caught during a control/eradication programme enables conservation managers to assess the reinvasion rates of their target species and evaluate the level of success of their control methods. We examine how genetic techniques can focus management by distinguishing between hypotheses of ‘reinvasion’ and ‘survivor’, and defining kin groups for invasive stoats ( M ustela erminea ) on S ecretary I sland, N ew Z ealand. 205 stoats caught on the island were genotyped at 16 microsatellite loci, along with 40 stoats from the opposing mainland coast, and the age and sex were determined for each individual. Using these data, we compare and combine a variety of genetic techniques including genetic clustering, population assignment and kinship‐based techniques to assess the origin of each stoat. The population history and individual movement could be described in fine detail, with results indicating that both in‐situ survival and breeding, and reinvasion are occurring. Immigration to the island was found to be generally low, apart from in 1 year where around 8 stoats emigrated from the mainland. This increased immigration was probably linked to a stoat population spike on the mainland in that year, caused by a masting event of southern beech forest ( N othofagus sp .) and the subsequent rodent irruption. Our study provides an example of some of the ways genetic analyses can feed directly into informing management practices for invasive species.

Pregnancy-related characteristics and breast cancer risk - Theodore M. Brasky; Yanli Li; David J. Jaworowicz; Nancy Potischman; Christine B. Ambrosone; Alan D. Hutson; Jing Nie; Peter G. Shields; Maurizio Trevisan; Carole B. Rudra; Stephen B. Edge; Jo L. Freudenheim (Cancer Causes & Control, 2013)

Recurrent violations of invariant rules for offspring size: evidence from turtles and the implications for small clutch size models - Njal Rollinson; Christopher B. Edge; Ronald J. Brooks (Oecologia, 2013)

Indicators of environmental stress: cellular biomarkers and reproductive responses in the Sydney rock oyster (Saccostrea glomerata) - Katelyn J. Edge; Emma L. Johnston; Anthony C. Roach; Amy H. Ringwood (Ecotoxicology, 2012)

Octopamine and serotonin have opposite effects on antipredator behavior in the orb-weaving spider, Larinioides cornutus - Thomas C. Jones; Tamer S. Akoury; Christopher K. Hauser; Michael F. Neblett; Brent J. Linville; Andrea A. Edge; Nathaniel O. Weber (Journal of Comparative Physiology A, 2011)

The effects of acute whole body vibration as a recovery modality following high-intensity interval training in well-trained, middle-aged runners - J. Edge; T. Mündel; K. Weir; D. J. Cochrane (European Journal of Applied Physiology, 2009)

Surface Energy of Microcrystalline Cellulose Determined by Capillary Intrusion and Inverse Gas Chromatography - D. Fraser Steele; R. Christian Moreton; John N. Staniforth; Paul M. Young; Michael J. Tobyn; Stephen Edge (The AAPS Journal, 2008)

A Field Test of the Quotient Method for Predicting Risk to Microtus canicaudus in Grasslands - G. Wang; W. Edge; J. O. Wolff (Archives of Environmental Contamination and Toxicology, 1999)

Organophosphate resistance in spider mites (Acari: Tetranychidae) from cotton in Australia - G.A. Herron; V.E. Edge; L.J. Wilson; J. Rophail (Experimental and Applied Acarology, 1998)